2020
DOI: 10.1111/jocn.15200
|View full text |Cite
|
Sign up to set email alerts
|

Consistency of postoperative pain assessments between nurses and patients undergoing enhanced recovery after gynaecological surgery

Abstract: Aims and objectives To explore the consistency of pain intensity and pain location assessed by nurses and patients in gynaecology undergoing enhanced recovery after surgery pathway. Background Several studies have shown that clinical nurses' assessment of patients' pain is not always accurate. Little is known about the accuracy of nurses' pain assessments for gynaecological patients. Postoperative pain assessment and management is an essential part of enhanced recovery after surgery. Design Comparative cross‐s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…Moreover, in the clinical setting, nurses' knowledge and practices are not always consistent [ 13 , 14 ]. They seem to normalize pain after surgery as an acceptable condition that patients have to suffer, leading to a lack of effort or priority in relieving the pain [ 13 , 15 ]. This causes a huge gap between nurses' perception and implementation in postoperative pain management, which possibly poses a great challenge to effective pain management in the hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in the clinical setting, nurses' knowledge and practices are not always consistent [ 13 , 14 ]. They seem to normalize pain after surgery as an acceptable condition that patients have to suffer, leading to a lack of effort or priority in relieving the pain [ 13 , 15 ]. This causes a huge gap between nurses' perception and implementation in postoperative pain management, which possibly poses a great challenge to effective pain management in the hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Patients who believe that the pain is of organic origin attribute the cause of pain to a neutral external factor and believe that damage or injury to the body causes pain (Pons et al, 2012;Ursavaş & Yaradılmış, 2020). A surgical incision that causes tissue trauma is one of the important reasons for postoperative pain, so the most severe pain is experienced at surgical incision sites (Blicfeldt-Eckhardt et al, 2014;Wang et al, 2018;Yang et al, 2020). However, patients who believe that pain is psychological attribute the cause of pain to internal factors and feelings affecting the experience of pain, such as depression and anxiety (Pons et al, 2012;Ursavaş & Yaradılmış, 2020).…”
mentioning
confidence: 99%
“…About 40% of all patients who admit in hospitals with traumatic brain injuries, rather to recover, their conditions get more worsen due to improper assessment and poor management (Arsh et al, 2017). Moreover, poor knowledge and ine cient skill performance of nurses was found associated with prolong hospital stay of patients in emergency departments and intensive care units (Yang et al, 2020). Another study found that lack of knowledge and ine cient skill regarding the GCS assessment was related to late recovery of patients in intensive care units (Gage et al, 2012).…”
Section: Introductionmentioning
confidence: 99%